PET/MR Imaging A Case-Based Approach - Gupta, Rajesh (Springer International Publishing, 2018)
This book offers an overview of the clinical applications of PET/MR imaging through a case-based format. Hybrid PET/MRI provides functional and anatomical information via one setting offering superior imaging quality with lower radiation dose being administered to the patient. The cases in this book focus on the use of this technique in the diagnosis of oncologic, neurologic, cardiovascular, infectious and inflammatory, and pediatric diseases. Each case is presented with the patient history, protocols, interpretation of findings, and pearls and pitfalls accompanied by high quality PET/MR images. The major strength of this book is the discussion of both MRI and PET findings pertinent to each particular case. It expands the discussion of oncologic applications of this modality through a variety of cases that highlight staging, treatment response, and follow up. Illustrating a spectrum of PET/MRI clinical applications, PET/MR Imaging: A Case-Based Approach is a valuable resource for radiologists, nuclear medicine physicians, and residents. .